Methodological thinking : basic principles of social research design - Loseke, Donileen R. (SAGE Publications, 2013)
Methodological Thinking: Basic Principles of Social Research Design focuses on the underlying logic of social research and encourages students to understand research methods as a way of thinking. The book provides an overview of the basic principles of social research, including the foundations of research (data, concepts, theory), the characteristics of research questions, the importance of literature reviews, measurement (conceptualization and operationalization), data generation techniques (experiments, surveys, interviews, observation, document analysis), and sampling. The text is organized to help students become good consumers and producers of research by developing skills to design small-scale research projects and evaluate research done by others. The author highlights the relationships among various components of research; she also explains that it is not possible to argue that one form of research is better than any other and that good researchers understand the differences among and appreciate the capabilities of different tools. Key Features Takes an interdisciplinary approach, with examples in criminology/criminal justice, sociology, political science/international relations, and social work Offers a balanced account of theoretical perspectives, providing students with an unbiased presentation Minimizes technical details of social research design to emphasize logic and general principles Explore the open-access Student Study Site, which features the full versions of the journal articles that are referenced throughout the book.